Influence of alkali treatment and nanoclay content on the properties of rice husk filled polyester composites - Nabinejad, O.; Debnath, Sujan; Ying, T.; Liew, W.; Davies, I. (2017)
The effect of alkali treatment and nanoclay addition on the mechanical properties and water absorption behavior of rice husk particle (RHP) reinforced unsaturated polyester (UP) composites was investigated. Thermogravimetric analysis (TGA) indicated that the alkali treatment removed most of the hemicellulose and impurities from the RHP with the tensile strength, tensile modulus, flexural strength and flexural modulus of the resulting composites being improved by alkali treatment. The results indicated that the 5% sodium hydroxide concentration had the optimum performance on mechanical strength and water absorption resistance. Furthermore, the influence of nanoclay addition (1, 3 and 5 wt%) on the properties of optimum alkali treated RHP-UP composites was investigated with the lowest content (1 wt%) of nanoclay showing the highest mechanical performance. However, further addition of nanoclay improved the moisture absorption resistance of the composites. Good interface bonding between the filler and matrix was observed from scanning electron micrographs for the optimum RHP alkali treated and nanoclay dispersed RHP-UP composites.